Centriolar Protein C2cd3 Is Required for Craniofacial Development - Chang, Ching-Fang; Brown, Kari M.; Yang, Yanfen; Brugmann, Samantha A. (Frontiers in Cell and Developmental Biology, 2021)
The primary cilium is a ubiquitous, microtubule-based cellular organelle. Primary cilia dysfunction results in a group of disorders termed ciliopathies. C2 domain containing 3 centriole elongation regulator (C2cd3), encodes a centriolar protein essential for ciliogenesis. Mutations in human C2CD3 are associated with the human ciliopathy Oral-Facial-Digital syndrome type 14 (OFD14). In order to better understand the etiology of ciliopathies including OFD14, we generated numerous murine models targeting C2cd3. Initial analysis revealed several tissue-specific isoforms of C2cd3, and while the loss of C2cd3 has previously been reported to result in exencephaly, tight mesencephalic flexure, pericardial edema, abnormal heart looping and twisted body, further analysis revealed that genetic background may also contribute to phenotypic variation. Additional analyses of a conditional allelic series targeting C-terminal PKC-C2 domains or the N-terminal C2CD3N-C2 domain of C2cd3 revealed a variable degree of phenotypic severity, suggesting that while the N-terminal C2CD3N-C2 domain was critical for early embryonic development as a whole, it was also important for craniofacial development. Together, through generation of novel models and evaluation of C2cd3 expression, these data provide valuable insight into mechanisms of pathology for craniofacial ciliopathies that can be further explored in the future.